Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/03601234.2013.816586
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of oxyfluorfen in aqueous methanol

Abstract: Photolysis of oxyfluorfen, an herbicide of the nitrodiphenyl ether class, was studied in aqueous methanol under UV and sunlight. UV irradiation was carried out in a borosilicate glass photoreactor (containing 250 ppm oxyfluorfen in 50% aqueous methanol) equipped with a quartz filter and 125 watt mercury lamp (maximum output 254 nm) at 25 ± 1°C. Sunlight irradiation was conducted at 28 ± 1°C in borosilicate Erlenmeyer flasks containing 250 ppm oxyfluorfen in 50% aqueous methanol. The samples from both the irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…There is very little research on the photodegradation remediation process of diphenyl ether compounds. Chakraborty et al [ 77 ] reported that the photodegradation products of oxyfluorfen may undergo ether bond cleavage and dehalogenation pathways. In the process of using TiO 2 to degrade acifluorfen, Xin [ 71 ] also confirmed the cleavage of ether bonds, dehalogenation, hydroxylation, and other products.…”
Section: Chemical Remediation Of Diphenyl Ether Herbicide Residual Co...mentioning
confidence: 99%
“…There is very little research on the photodegradation remediation process of diphenyl ether compounds. Chakraborty et al [ 77 ] reported that the photodegradation products of oxyfluorfen may undergo ether bond cleavage and dehalogenation pathways. In the process of using TiO 2 to degrade acifluorfen, Xin [ 71 ] also confirmed the cleavage of ether bonds, dehalogenation, hydroxylation, and other products.…”
Section: Chemical Remediation Of Diphenyl Ether Herbicide Residual Co...mentioning
confidence: 99%
“…The main transformation pathways of oxyfluorfen involved nitro reduction, dechlorination, hydrolysis, and nucleophile displacement reaction. [65] Interaction between Cd C2 and the insecticide CPF in inducing hepatoxicity was studied by allowing 0.01-M solutions of each to react in ethyl acetate or deionized water under slow mixing for 24 h. The mixture was analyzed by TLC on silica gel plates developed with ethyl acetate-hexane (30:70) followed by visualization by exposure to iodine and viewing under UV light. It was demonstrated that joint hepatoxicity of Cd ion and CPF was chiefly due to the Cd-CPF complex-facilitated intercellular transport associated with oxidative stress under environmental and biological settings, posing substantial health risk by cooccurrence to humans.…”
Section: Tlc-msmentioning
confidence: 99%